Customer Relationship Marketing / Get to Know Your Customers and Win their Loyalty - Machtynger Liz; Stone Merlin; Woodcock Neil (Kogan Page Limited, 2002)
The best practical introduction to customer relationship marketing (CRM). Acknowledgements, Preface, Foreword, Why Relationship Marketing, Models of Customer Management, The Customers' Perspective, The Company's Perspective, Quantifying the Impact, Identifying Customers' Relationship Needs, The Role of Market Research, Customer Retention and Loyalty, Integrating CRM Strategies, Processes and Procedures, People and Performance, CRM Technology - Today and Tomorrow, The Future of e-CRM, CRM Program, Planning, Index.